2019
DOI: 10.1093/nar/gkz726
|View full text |Cite
|
Sign up to set email alerts
|

USP11 acts as a histone deubiquitinase functioning in chromatin reorganization during DNA repair

Abstract: How chromatin dynamics is regulated to ensure efficient DNA repair remains to be understood. Here, we report that the ubiquitin-specific protease USP11 acts as a histone deubiquitinase to catalyze H2AK119 and H2BK120 deubiquitination. We showed that USP11 is physically associated with the chromatin remodeling NuRD complex and functionally involved in DNA repair process. We demonstrated that USP11-mediated histone deubiquitination and NuRD-associated histone deacetylation coordinate to allow timely termination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 101 publications
4
52
0
Order By: Relevance
“…In support of this, RNF8 depleted cells showed a delay in IR-induced 53BP1 foci, as expected, while depletion of USP11 led to hyperaccumulation of ubiquitin conjugates and 53BP1 [ 33 ]. Although this work argues that USP11 is specific for ubiquitinated γH2AX, others have shown USP11 activity towards H2AK119ub1 as well as H2BK120ub1 [ 137 ]. In these studies, the defects in DSB repair and IR sensitivity observed upon loss of USP11 were restored when USP11 was co-depleted with either BMI1 or RNF20 (involved in catalyzing H2AK119ub1 and H2BK120ub1, respectively) [ 137 ].…”
Section: The Reversal Of Histone Ubiquitination At Dsbsmentioning
confidence: 93%
See 3 more Smart Citations
“…In support of this, RNF8 depleted cells showed a delay in IR-induced 53BP1 foci, as expected, while depletion of USP11 led to hyperaccumulation of ubiquitin conjugates and 53BP1 [ 33 ]. Although this work argues that USP11 is specific for ubiquitinated γH2AX, others have shown USP11 activity towards H2AK119ub1 as well as H2BK120ub1 [ 137 ]. In these studies, the defects in DSB repair and IR sensitivity observed upon loss of USP11 were restored when USP11 was co-depleted with either BMI1 or RNF20 (involved in catalyzing H2AK119ub1 and H2BK120ub1, respectively) [ 137 ].…”
Section: The Reversal Of Histone Ubiquitination At Dsbsmentioning
confidence: 93%
“…Although this work argues that USP11 is specific for ubiquitinated γH2AX, others have shown USP11 activity towards H2AK119ub1 as well as H2BK120ub1 [ 137 ]. In these studies, the defects in DSB repair and IR sensitivity observed upon loss of USP11 were restored when USP11 was co-depleted with either BMI1 or RNF20 (involved in catalyzing H2AK119ub1 and H2BK120ub1, respectively) [ 137 ]. This reveals several additional mechanisms by which USP11 may influence DSB repair including transcriptional regulation and chromatin conformation.…”
Section: The Reversal Of Histone Ubiquitination At Dsbsmentioning
confidence: 93%
See 2 more Smart Citations
“…USP11 participates in processes such as TGFβ signaling, pro-inflammatory signaling, viral replication and NF-κB signaling by regulating the protein stability of various targets such as ARID1A, TβRII, CDKN2A, RAE1, XIAP, HPV16-E7 and IκBα (Luo et al, 2020, Deng et al, 2018, Jacko et al, 2016, Lin et al, 2008, Sun et al, 2010, Stockum et al, 2018. USP11 also functions in DSB repair, wherein USP11 deubiquitinates H2AX to regulate the recruitment of RAD51 and 53BP1 to damage foci (Ting et al, 2019, Yu et al, 2016. USP11 deubiquitinates PALB2 and promotes BRCA1-PALB2-BRCA2 complex formation (Orthwein et al, 2015).…”
Section: Introductionmentioning
confidence: 99%